Application of Vertical Gravity Gradient to Delineate Groundwater Damage at Bandung Basin. Issue 1 (1st May 2022) - Abdurrahman, Dadi; Setianingsih,; Santoso, Djoko; Kadir, Wawan Gunawan A.; Dahrin, Darharta; Isniarno, Noor Fauzi; Amukti, Rian
Abstract: Bandung basin is the center of the population at West Java, and several Industrial areasis. In supporting its sustainability, water needs is one of the factors that must be fulfilled. The water needs are obtained by taking water directly from groundwater. Excessive extraction of groundwater can cause damage, the impact of which is the more difficult it is to obtain groundwater and cause environmental disaster in the form of land subsidence. Using the vertical gravity gradient technique in the Bandung basin area is expected to map the critical groundwater damage zone. The results from the vertical gravity gradient area of the Bandung basin map, the region of groundwater with critical status are found in almost all cities, except in the Baleendah area to Ciparay and Soreang to the south of Cimahi.